An approach to Paraguayan organized groups in Buenos Aires - Halpern, Gerardo (2008)
In this article I will try to introduce some of the aspects that compose what is commonly known as 'Paraguayan community in Argentina'. Nonetheless, the underlying hypothesis of these considerations assumes that much of such referent transcends what common sense ascribes to it; the so-called 'Paraguayan community' shows dynamics and processes that are often disregarded by the social imagery. Hence, I will herein intend to point out some of the motives and reasons that explain such disregard and, at the same time, collaborate in building up the definitions I will subsequently propose.